META-ANALISIS : MODEL-MODEL PEMBELAJARAN DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Saroiroh, Alfi (BIO-EDU: Jurnal Pendidikan Biologi, 2022)
Critical thinking skills are thinking based on facts, which are meaningful, as well as thinking based on goals and reasons. Critical thinking skills are used in developing ideas from a problem. Critical thinking skills that have been studied so far are only limited to knowing whether or not the influence of the learning model on critical thinking skills at certain levels of education. No research has been found that examines the tendency of various learning models and levels of education in improving critical thinking skills. The research objectives are: (1) to determine the potential of the learning model in improving critical thinking skills, (2) to determine the factors that influence the strength or weakness of the learning model on critical thinking skills. This type of research is a meta-analytical survey of quasi-experimental research, learning model as the independent variable and critical thinking skills as the dependent variable. The data analyzed were 50 studies consisting of 2 articles, 12 theses, 29 theses, and 7 dissertations. The results showed that 47 studies had an effect on improving students' critical thinking. Most studies use innovative learning models in improving critical thinking. The learning model contains a learning syntax that contains strategies to improve critical thinking skills. The conclusion of the research is that most of the learning models in improving critical thinking skills are innovative learning models. Other factors that influence critical thinking skills are syntax excellence, teacher's ability to teach, condition, and students' intelligence.